OLOCASIA BASED CROPPING SYSTEMS AFFECTS THE ANTIOXIDANT PROPERTIES AND PRODUCTIVITY OF COLOCASIA [COLOCASIA ESCULENTA (L.) SCHOTT] TUBER - M. D. TUTI; R. S. PAL; R. ARUN KUMAR; J. K. BISHT; J. C. BHATT (The Bioscan, 2015)
Four colocasia based cropping system viz Colocasia-Onion-Frenchbean (C-O-F), Colocasia-Frenchbean-Potato (C- F-P), Colocasia-Cabbage-Frenchbean (C-Ca-F), Colocasia-Coriander-Tomato (C-Co-T) were taken to find out the effect of different crops under colocasia based cropping system on the antioxidant activities (AA) and productivity of colocasia tuber. The highest concentrations of phenolics (0.966 + 0.009 mg gallic acid equivalent /100 mg fresh weight) and condensed tannins (0.022 + 0.001 mg catechins equivalent /100 mg fresh weight) were found in ‘C-O-F’, while the anthocyanin (4.29 + 0.04 mg/100 mg fresh weight) were found highest for ‘C-Co-T’ cropping system. Colocasia samples from ‘C-O-F’ cropping system showed highest DPPH and ABTS radical scavenging activities, while reducing power activity was found highest in the colocasia samples from ‘C-Co-T’ cropping system. Principal component analysis (PCA) showed strong correlation between phenolics, tannins and AA, while anthocyanin was found positively correlated with reducing power. Results of the finding provides evidence that the colocasia samples for ‘C-O-F’ cropping system showed higher antioxidant activities than samples from other cropping system in most of the determinations, while the productivity in terms of colocasia equivalent yield (52.38 ton/ha) was recorded highest in the ‘C-O-F’ cropping system.